Modal Sosial Dalam Pengelolaan Hutan Adat Negeri Hutumuri Kecamatan Leitimur Selatan Kota Ambon - Silooy, Hilery G; Tjoa, Marthina; Iskar, Iskar (Tropical Small Island Agriculture Management, 2024)
The purpose of this research is to find out the forms of social capital and the role of indigenous peoples in customary forest management. To analyze the elements of social capital in customary forest management in Hutumuri Country. The method used in this research is a descriptive method with a qualitative and quantitative approach. The results of the study show that the Hutumuri community believes in existing rules (written and unwritten rules) that the Hutumuri community builds and maintains social relations in one country on the basis of kinship and neighborly social relations that also take place between members of the Hutumuri community and members of neighboring communities Social capital! in the Hutumuri community, it is measured by its elements, Belief in the network. Social norms of solidarity are quite strong, the level of trust among members of the Hutumuri community is high. They trust each other among their members.